INFORMATICS EDUCATION IN DIFFERENT DISCIPLINES AT UNIVERSITY LEVEL CASE STUDY: A SURVEY OF STUDENTS' ATTITUDE TOWARD INFORMATICS TECHNOLOGIES - (:unkn) unknown (TURKISH ONLINE JOURNAL EDUCATIONAL TECH-TOJET, 2011)
This article presents a quantitative study on attitudes toward the usage of Information Technology related tools and applications. The study was conducted at a private university, Turkey, with 97 female and 113 male students involved as participants. They were each presented with a questionnaire to relate their attitudes toward IT and after undergoing a discrete IT course for the duration of one semester (15 weeks). The attitudes of the respondents were measured in terms of three dimensions, namely, usefulness, confidence and learning. Both genders exhibited the same levels of attitudes after undergoing the comprehensive IT course. The largest improvement for females and males was in the learning dimension which showed that their initial dislike toward IT was greatly reduced at the end of the course. In terms of confidence, female and male participants exhibited an enhanced confidence level after the course. One area of information technology quickly becoming ultimate is the field of Informatics. Information technology is the area of managing technology and spans wide variety of areas that include but are not limited to things such as processes, computer software, information systems, computer hardware, programming languages, and data constructs. To meet this growing need universities are beginning to develop degree programs with the integration of Informatics. In response to the widespread use of and ever-changing nature of Informatics, various investigations were carried out regarding attitudes toward informatics. Employing people who understand Informatics is a top priority for industries, business, government, education and the military sectors. Informatics can be defined as the multidimensional use of technology to support knowledge discovery assisting the decision maker to achieve the organizational goals. Informatics incorporates the way data is collected, organized, analyzed, represented, filtered and managed. Totally this paper attempted to investigate university student attitudes toward the integration of Informatics Technology in their departments and factors contributing to their attitudes so as to provide some constructive information and suggestions for the adoption of technology in informatics education.